From models to SMEFT and back? - Brivio, Ilaria; Bruggisser, Sebastian; Geoffray, Emma; Killian, Wolfgang; Krämer, Michael; Luchmann, Michel; Plehn, Tilman; Summ, Benjamin (SciPost physics, 2022)
We present a global analysis of the Higgs and electroweak sector, in the SMEFT framework and matched to a UV-completion. As the UV-model we use the triplet extension of the electroweak gauge sector. The matching is performed at one loop, employing functional methods. In the SFitter analysis, we pay particular attention to theory uncertainties arising from the matching. Our results highlight the complementarity between SMEFT and model-specific analyses.
Gesehen am 15.07.2022